Reconstruction of cyclic Mesozoic-Cenozoic stress development in SE Germany using fault-slip and stylolite inversion - Köhler, Saskia; Duschl, Florian; Fazlikhani, Hamed; Köhn, Daniel; Stephan, Tobias; Stollhofen, Harald (Geological Magazine, 2022)
The Franconian Platform of SE Germany and the underlying Permian and Triassic rocks that developed from latest Permian to Triassic time were affected by multiple compressional and extensional events that created a complex fracture, fault and stylolite network. We reconstructed the spatio-temporal variations of post-Triassic palaeostress fields in the Franconian Platform and Triassic strata using fault-slip and tectonic stylolite inversion. Our highly resolved stress inversion enables us to demonstrate a cyclic stress evolution from the stress regime of normal faulting to thrusting, strike-slip and back to normal faulting. Five main stress fields correlating with two stress cycles are determined for Late Jurassic to Cenozoic time. The first cycle consists of: (SF1) an initially NE-SW-directed horizontal extension during Late Jurassic to Early Cretaceous time; (SF2) NNE-SSW-directed horizontal compression with an early set of tectonic stylolites prior to the development of reverse and thrust faults; and (SF3) a strike-slip-dominated setting with (N)NE-(S)SW horizontal compression representing a first relaxation. The second cycle comprises (SF4) NW-SE-directed horizontal extension during Oligocene-Miocene time; and (SF5) a second strike-slip-dominated regime with WNW-ESE to NW-SE horizontal compression during the Alpine shortening, creating the youngest set of tectonic stylolites. In addition, we consider the transitional stages between thrusting and a strike-slip regime as a snapshot in the process of intraplate tectonics.
CRIS-Team WoS Importer:2022-08-26

Using Thermal Springs to Quantify Deep Groundwater Flow and Its Thermal Footprint in the Alps and a Comparison With North American Orogens - Luijendijk, Elco; Winter, Theis; Köhler, Saskia; Ferguson, Grant; von Hagke, Christoph; Scibek, Jacek (Geophysical Research Letters, 2020)
The extent of deep groundwater flow in mountain belts and its thermal effects are uncertain. Here, we use a new database of discharge, temperature, and composition of thermal springs in the Alps to estimate the extent of deep groundwater flow and its contribution to the groundwater and heat budget. The results indicate that thermal springs are fed exclusively by meteoric water and make up 0.1% of the total groundwater budget. Spring water circulates on average to a depth of at least 2 km. The net heat extracted from the subsurface equals 1% of the background heat flow, which equals an average thermal footprint of 7 km2. Cooling by downward flow and heating by upward flow are three and two times higher than the net heat flow, respectively. Comparison with North American orogens shows that hydrothermal activity is higher in areas with high relief or areas under extension.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Alps; groundwater; heat flow; thermal springs